Accounting Statements and Their Transformation - Koryagin, M. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The necessity for studying the current performance of the accounting statements system, finding out its transformation trends and justifying the vectors for its further improvement are substantiated. The existing approaches to defining the trends in the development of accounting statements are investigated, and their critical analysis is made. The author’s classification of trends in the development of accounting statements are developed taking into account changes in user’s requests for the accounting information. The problems and disadvantages of the existing accounting systems (financial, managerial, and strategic) are identified and further directions and prospects for their development are highlighted. The attention is focused on further directions of the development of accounting systems, which will elevate the accounting science on a new level of quality and ensure compliance of the accounting theory with the requirements of modern accounting and management practices. The essential tendencies in the development of accounting statements, which are insufficiently explored, and the vectors for modernization of the accounting system, not well-grounded in terms of creating new types, formats and forms of accounting statements, are outlined. It is found that a general classification of trends in the development of accounting statements has not existed by now, which does not allow for creating a general picture of research issues in this area. Not only the current trends in the development of accounting statements, but their backgrounds and impact on building a general classification of trends in the development of financial statements are analyzed. It is concluded that building of a classification of trends in the development of accounting statements has an important theoretical and practical value for the further development of accounting, because it will allow for to deeper understanding of the essence of various phenomena involved in the development of accounting statements.